2011
DOI: 10.1148/radiol.11100586
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Liver Function with Use of Gadoxetate Disodium–enhanced MR Imaging

Abstract: Quantitative evaluation of liver function by use of gadoxetate disodium (Gd-EOB-DTPA)-enhanced MR Imaging. Manuscript type: Original research Advance in Knowledge:The liver function corresponding to the plasma disappearance rate of indocyanine green (ICG-PDR) can be estimated quantitatively (R = 0.87) from the signal intensities and the volumes of the liver and the spleen on gadoxetate disodium-enhanced MR images. Implications for Patient Care:1. Our study results suggest that (Gd-EOB-DTPA)-enhanced MR imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
145
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(154 citation statements)
references
References 30 publications
5
145
1
1
Order By: Relevance
“…2,[8][9][10][11][12] The use of hepatobiliary-phase images for the evaluation of hepatic function has also been suggested. 13,14 The approved package insert dose of gadoxetic acid, 0.025 mmol/kg, yields a quarter of the dose of gadolinium of traditional formulation agents, including gadopentetate dimeglumine, gadoteridol, gadodiamide, gadoversetamide, and gadobenate dimeglumine. 15 This dose was determined based on preclinical studies 16,17 that demonstrated comparable early enhancement of hypervascular tumors between MRI with a 0.025 mmol/kg dose showed comparable early enhancement of hypervascular tumors to gadopentetate dimeglumine 16 A dose of 0.025 mmol/kg was also found to be the minimum effective dose during the hepatobiliary phase for the detection and characterization of lesions.…”
Section: Introductionmentioning
confidence: 99%
“…2,[8][9][10][11][12] The use of hepatobiliary-phase images for the evaluation of hepatic function has also been suggested. 13,14 The approved package insert dose of gadoxetic acid, 0.025 mmol/kg, yields a quarter of the dose of gadolinium of traditional formulation agents, including gadopentetate dimeglumine, gadoteridol, gadodiamide, gadoversetamide, and gadobenate dimeglumine. 15 This dose was determined based on preclinical studies 16,17 that demonstrated comparable early enhancement of hypervascular tumors between MRI with a 0.025 mmol/kg dose showed comparable early enhancement of hypervascular tumors to gadopentetate dimeglumine 16 A dose of 0.025 mmol/kg was also found to be the minimum effective dose during the hepatobiliary phase for the detection and characterization of lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the signal intensity of Gd-EOB-enhanced MRI is influenced, for example, by the degree of fibrosis as a result of a changed distribution volume of the T1 contrast agent and changed relaxivity in the extracellular space or by the fat or iron content. However, these seem to be negligible due to fast gradient echo sequences with short echo times and the use of relative enhancement [51].…”
Section: Mri As Imaging-based Liver Function Testmentioning
confidence: 99%
“…In human studies, liver parenchymal enhancement after administration of Gd-EOB-DTPA has been shown to correlate with ICG clearance and with liver cirrhosis as assessed by the CPS [26,27], and subsequent biliary excretion has been shown to be delayed in patients with impaired liver function [28]. In a study of patients with primary biliary cirrhosis, quantitative parameters indicative of liver function derived from DA were shown to correlate with disease severity [29].…”
mentioning
confidence: 99%